2022
DOI: 10.1371/journal.pone.0262438
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cytokine storm on severity of COVID-19 disease in a private hospital in West Jakarta prior to vaccination

Abstract: Background and aim Coronavirus Disease 2019 (COVID-19) has become a worldwide pandemic and is a threat to global health. Patients who experienced cytokine storms tend to have a high mortality rate. However, to date, no study has investigated the impact of cytokine storms. Materials and methods This retrospective cohort study included only COVID-19 positive patients hospitalized in a Private Hospital in West Jakarta between March and September 2020. All patients were not vaccinated during this period and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
1
12
0
2
Order By: Relevance
“…A key determinant factor of COVID19 progression is the uncontrolled dysregulation production of cytokines and chemokines, resulting in the development of a cytokine storm, systemic inflammation, and consequently multi-organ failure ( 2 ). The presence of the cytokine storm was associated with COVID-19 severity as previously reported ( 3 , 4 ), where the serum levels of cytokines in COVID-19 patients were significantly correlated with the severity of the disease and acted as warning indicators of the severity and progression of COVID-19.…”
Section: Introductionsupporting
confidence: 79%
“…A key determinant factor of COVID19 progression is the uncontrolled dysregulation production of cytokines and chemokines, resulting in the development of a cytokine storm, systemic inflammation, and consequently multi-organ failure ( 2 ). The presence of the cytokine storm was associated with COVID-19 severity as previously reported ( 3 , 4 ), where the serum levels of cytokines in COVID-19 patients were significantly correlated with the severity of the disease and acted as warning indicators of the severity and progression of COVID-19.…”
Section: Introductionsupporting
confidence: 79%
“…Research about the mechanisms underlying COVID-19 immunopathology early identified IL-6 as a deleterious factor and proposed this cytokine as one of the main therapeutic targets to be blocked to improve patient survival and outcome. Following this direction, two IL-6 receptor antagonists, tocilizumab and sarilumab have been used in COVID-19 with variable outcomes ( 54 57 ). We found that IL-6 was significantly associated with death by COVID-19 only during the first wave leading us to question the role of this cytokine as a single biomarker associated with fatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Many COVID-19 patients who exhibit severe SARS-CoV-2 infection are admitted to critical care units and have very high concentrations of inflammatory markers and D-dimers in their serum samples [ 21 ]. When evaluating the results of blood tests on patients with severe SARS-CoV-2 infection, it was observed that a very large increase in cytokines, roughly equivalent to an increase of four times or more, is associated with an increased risk of mortality [ 22 ]. Additionally, the severity of COVID-19 may be impacted by a number of known and unknown variables, such as certain demographic features, racial disparities, the poverty status of the community, or an ethnic group such as the Roma population.…”
Section: Introductionmentioning
confidence: 99%